El aula rural: un espacio para aprender juntos - Ligia María Angulo-Hernández; Yadira Cerdas-Rivera; Sandra Ovares-Barquero (Universidad Nacional, Costa Rica, 2004)
This article summarizes the most significant results of research carried out with two female teachers and a male teacher who work is school whit only one instructor located in the Pacific, Atlantic and Central areas of the country. Through case studies, the aim is to analyze the forms of interaction used by the rural teacher and how such an interaction favors or affects the student's learning process, emphasizing or not on the results that were found to be relevant and which enable the understanding of rural male and female teachers' work, especially of those who teach by themselves. Gender mainstreaming and values are tools that allow for social change, they are essential agents in an individual's education. When dealing whit aspects of society and values, this theory provides the teacher whit the possibility of experiencing social reality from a more human, supportive and tolerant point of view. For this reason, the incorporation of these elements in the course outline is essential.